Pengaruh Tax Avoidance dan Profitabilitas Terhadap Nilai Perusahaan dengan Kebijakan Hutang Sebagai Variabel Pemoderasi - Adelia, Elsa Wahyu; Sumaryati, Anna (Akuisisi : Jurnal Akuntansi, 2025)
The purpose of this study is to investigate the impact of tax avoidance and profitability on firm value by using debt policy as a moderating factor. The research sample comprises of 34 energy businesses that were listed on the Indonesia Stock Exchange between 2020 and 2022, and were chosen through a selective selection technique. This study approach focuses on the utilization of secondary data, with data analysis performed using Warp PLS version 8.0 software. The Cash Effective Tax Rate (CETR) variable measures tax avoidance, while the Return on Assets (ROA) ratio measures profitability. Tobin's Q is a measure of firm value, while the Debt to Equity Ratio (DER) is a measure of debt policy. Based on research findings, tax avoidance and profitability can have an impact on company value. Debt policy is able to strengthen the impact of tax avoidance on company value, but debt policy cannot strengthen the impact of profitability on company value. Energy sector companies are considering debt policy strategies more carefully to optimize company value through tax avoidance practices.